ISOLASI DAN IDENTIFIKASI SENYAWA ALKALOID DALAM EKSTRAK ETANOL DAUN PANDAN HUTAN JENIS BARU (Freycinetia sessiliflora Rizki) - Ade Ferdinan; Fitri Sri Rizki; Nunik Rahmawati (Akademi Farmasi Yarsi Pontianak, 2021)
Purpose of this research to isolate and identify the alkaloid compounds found in forest pandan leaves (Freycinetia sessiliflora Rizki). Phytochemical screening using Mayer, Dragendorff and Wagner reagents, phytochemical screening results for alkaloids with two reagents showed positive results, there is brownish orange precipitate on Dragendorff's reagent and yellow to brownish precipitate on Wagner's reagent. Isolation using Thin Layer Chromatography (TLC) and Column Chromatography with ethyl acetate: methanol: NH4OH (85: 10: 5), showing Rf values of 0.25-0.62. Wavelength analysis using UV-Vis spectrophotometry showed that the content of forest pandan leaf alkaloid compounds (Freycinetia sessiliflora Rizki) was at a wavelength of 262-266 nm.